Unifying macroecology and macroevolution to answer fundamental questions about biodiversity. Issue 12 (6th November 2019) - McGill, Brian J.; Chase, Jonathan M.; Hortal, Joaquín; Overcast, Isaac; Rominger, Andrew J.; Rosindell, James; Borges, Paulo A. V.; Emerson, Brent C.; Etienne, Rampal S.; Hickerson, Michael J.; Mahler, D. Luke; Massol, Francois; et al.
Abstract: The study of biodiversity started as a single unified field that spanned both ecology and evolution and both macro and micro phenomena. But over the 20th century, major trends drove ecology and evolution apart and pushed an emphasis towards the micro perspective in both disciplines. Macroecology and macroevolution re‐emerged as self‐consciously distinct fields in the 1970s and 1980s, but they remain largely separated from each other. Here, we argue that despite the challenges, it is worth working to combine macroecology and macroevolution. We present 25 fundamental questions about biodiversity that are answerable only with a mixture of the views and tools of both macroecology and macroevolution.